Resveratrol plus carboxymethyl-β-glucan in infants with common cold: A randomized double-blind trial. Issue 4 (April 2020) - Baldassarre, Maria Elisabetta; Di Mauro, Antonio; Labellarte, Grazia; Pignatelli, Mariacristina; Fanelli, Margherita; Schiavi, Elisa; Mastromarino, Paola; Capozza, Manuela; Panza, Raffaella; Laforgia, Nicola
Abstract: Objectives: To evaluate effectiveness of a nasal resveratrol/carboxymethyl-β-glucan solution compared to nasal saline solution: a) on common cold symptoms by means of a validated measure scale (CARIFS score), b) on Rhinovirus infection and CCL2, CCL5, IL8, IL6, CXCL10 and TLR2 expression in nasal swabs, c) on frequency of relapses after 30 days of follow-up. Methods: 89 infants with respiratory infection symptoms were randomly assigned to receive either a nasal resveratrol/carboxymethyl-β-glucan solution or nasal saline solution. All patients were evaluated with CARIFS score at enrollment, after 48 h, 7 and 30 days by physicians and parents. Nasal swabs were obtained at enrollment, after 48 h and after one week. Results: CARIFS score improved in both groups. Episodes of sneezing and cough were fewer in study group after 7 days of follow-up (p < 0.05). No significant differences were found on nasopharyngeal swabs in Rhinovirus detection and cytokines expression after 48 h, nor in 30 days relapses. TLR2 expression was significantly higher in Rhinovirus infected children of the study group. No adverse effects occurred. Conclusions: These data suggest that a solution containing resveratrol plus carboxymethyl-β-glucan might have a positive impact on both clinical and socio-economic burden due to infant common cold. Abstract : "Common cold" [Mesh]; Resveratrol/carboxymethyl-β-glucan; "Rhinovirus" [Mesh]; Biological science; Natural product; Antioxidant; Molecular biology; Biomolecules; Microbiology; Natural product chemistry; Toxicology; Pharmaceutical science.